Anemia of Chronic Disease in Rheumatoid Arthritis and its Relationship with Disease Activities - Islam, Md Rofiqul; Islam, Md Shafiqul; Sultana, Mst Musarrat (TAJ: Journal of Teachers Association, 2020)
Background: Rheumatoid arthritis is the most common form of inflammatory arthritis. Anemia is a common extra-articular manifestation and anemia of chronic disease (ACD) is the most common form of anemia in rheumatoid arthritis that reduces the quality of life. Objectives: The purpose of this study was to find out the prevalence of anemia of chronic disease (ACD) in Rheumatoid arthritis and to determine the relationship between ACD and disease activity of rheumatoid arthritis patients and to Identify the relationship between ACD and disease activity of rheumatoid arthritis patients. Methods: This was an observational cross-sectional study was conducted at the Department of Medicine, Rajshahi Medical College Hospital, Rajshahi. Consecutive 165 patients of rheumatoid arthritis with anemia who fulfilled the inclusion and exclusion criteria were enrolled in this study. Results: In this study mean age of these patients was 43.2±13.5 years. Male were 27(16.4%) and female 135(83.6%) with male: female ratio was 1:5.1. Most of the patients (29.1%) were illiterate, maximum participants (81.8%) were married and housewife 73.3%. DAS- 28 score (p< 0.001), tender and swollen joint count (p<0.001 for both tender and swollen joint count), ESR (p< 0.001) and HAQ score (p< 0.001) were significantly higher in anemic group of patients as compared to non-anemic. But there was no significant difference in terms of disease duration, morning stiffness and RF positivity between mentioned groups (p> 0.05). Comparing disease activity related characteristics between pure ACD and ACD with co-existent IDA sub group of patients, DAS 28 (p< 0.001), tender joint count (p= 0.03), swollen joint count (p= 0.03) and HAQ score (p= 0.03) were significantly higher in pure ACD patients than ACD and concomitant IDA patients with RA. But no significant difference was observed between two subgroups in terms of disease duration, morning stiffness, ESR and RF positivity (p> 0.05).Comparison of disease activity indices at different cut off levels between two groups and subgroups. Higher DAS- 28 score, tender joint count, swollen joint count and HAQ score was significantly found in anemic group of patients as compared to non-anemic. No significant difference was found between two groups at differing levels of morning stiffness (p= 0.337). Conclusions: ACD is frequently encountered with high frequency of iron deficiency anemia among rheumatoid arthritis patients and RA patients with anemic tend to have more severe disease than non-anemic RA patients. TAJ 2020; 33(2): 85-93